ASESMEN KOMPETENSI KARYAWAN BANK PERKREDITAN RAKYAT KABUPATEN ROKAN HULU, PROVINSI RIAU - Achmad Tavip Junaedi; Sudarno Sudarno; Suhardjo Suhardjo; Evelyn Wijaya; Martha Ng (LPPM Universitas Abdurrab, 2023)
Employees are an important part of organization that is able to mobilize and synergize other resources to achieve organizational goals. The success of organization is largely determined by the roles and functions of the employees in it. Therefore, the organization must empower all components of employees who are well owned in order to be able to improve performance by carrying out the employee competency assessment process based on the intended function and position. Competency assessment activities for employees of Rokan Hulu Rural Bank were carried out on 16-17 July 2022 with a total of 32 participants. This PKM activity aims to evaluate employee competence based on the intended function and position. Employee competency assessment will be carried out on prospective employees, permanent employees, section heads, and branch heads based on psychological aspects and managerial competency aspects. The PKM results showed that 23 participants were in the Still Qualified (MMS) category, 5 participants were in the Qualified (MS) category and 4 participants were in the Less Qualified (KMS) category. Thus overall there were 28 participants who were suggested for promotion to the intended position and 4 participants who were not advised to be promoted to the intended position.